(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The main methodological aspects of the organization of the distance learning system (DLS). First of all, we give the concept of distance learning, which takes into account the characteristic features and options for organizing distance learning to a greater extent. Distance learning is a humanistic form of learning, based on the use of a wide range of traditional and new pedagogical and information technologies based on technical means that are used to independently study the educational material and organize dialogue exchange between the teacher and the student.